Intrinsically 32P‐Labeled Diamond Nanoparticles for In Vivo Imaging and Quantification of Their Biodistribution in Chicken Embryos. (23rd July 2018) - Happel, Patrick; Waag, Thilo; Schimke, Magdalena; Schweeberg, Sarah; Muzha, Andreas; Fortak, Katrin; Heesch, Daniel; Klask, Laura; Pilscheur, Mathias; Hoppe, Franziska; Lenders, Thomas; Meijer, Jan; et al.
Abstract: Nanoparticles, especially from carbon, have great potential in biomedicine. However, prior to clinical use, biocompatibility and biodistribution of these nanoobjects have to be assessed. Currently, particle detection is mostly based on surface‐bound labels, inevitably altering materials' properties by surface modification. Further obstacles include bleaching, dissociation of labels from the surface, weak emission of fluorophores due to insufficient tissue opacity or hampered light penetration or the need for specific excitation wavelengths. These characteristics greatly constrain employment of such nanoparticles to address complex analytical questions. To overcome these drawbacks, the use of intrinsic structural features of nanoobjects is highly desirable: the particle surface remains unchanged and the nanoobject exhibits its innate behavior. Thus, for sensitive detection and quantification, labels should be incorporated in the nanoparticle core, thereby avoiding cleavage and warranting unchanged surface characteristics. The incorporation of clinically approved radionuclide 32 P into the lattice of nanodiamond particles using highly defined ion implantation is described here. The properties, uptake, and biodistribution are studied in vivo, in the developing hen's egg model (hen's egg test on chorioallantoic membrane assay). It is found that 32 P labeling of diamond nanoparticles allows their reliable localization and sensitive quantification in a cost efficient, highly reliable, and safe way using available autoradiographic devices and analytical methods. Abstract : Intrinsic labeling of nanodiamonds with 32 P using ion implantation into nanodiamonds embedded in a soluble and inert matrix is described. Biodistribution is quantitatively measured in a developing hen's egg model and in vivo imaging of the nanoparticles is demonstrated to be independent of light penetration, providing access through thick layers of tissue.